Cerebral sparganosis in children: epidemiological, clinical and MR imaging characteristics - Gong, Caigui (BioMed Central, 2012)
BACKGROUND: Cerebral sparganosis in children is an extremely rare disease of central nervous system, and caused by a tapeworm larva from the genus of Spirometra. In this study, we discussed and summarized epidemiological, clinical and MR imaging characteristics of eighteen children with cerebral sparganosis for a better diagnosis and treatment of the disease. METHODS: Eighteen children with cerebral sparganosis verified by pathology, serological tests and MR presentations were retrospectively investigated, and the epidemiologic and clinical characteristics of the disease were studied. RESULTS: Twenty-seven lesions were found in the eighteen children. Twelve lesions in twelve patients were solitary while the lesions in the rest six patients were multiple and asymmetrical. The positions of the lesions were: seven in frontal, eleven in parietal, four in temporal and two in occipital lobes, one in basal ganglia, one in cerebella hemisphere and one in pons. The lesions were presented as slight hypointensity on T1-weighted images but moderate hyperintensity on T2-weighted images with perilesional brain parenchyma edema. Enhanced MR scans by using Gadopentetic Acid Dimeglumine Salt were performed in the patients, and the images demonstrated abnormal enhancements with the patterns of a peripheral ring, or a tortuous beaded, or a serpiginous tubular shape. Follow-up MR scans were preformed for eight patients, and three out of the eight cases exposed migrations and changes in shapes of the lesion areas. CONCLUSIONS: The MR presentations in our study in general were similar to those in previous studies. However serpiginous tubular and comma-shaped enhancements of lesions have not been previously reported. The enhanced MR imaging and follow-up MR scans with the positive results from serological tests are the most important methods for the clinical diagnosis of cerebral sparganosis in children.